The usage of the method of mathematical statistics in the process of optimization of the content of antifriction composite materials - Zinchenko, D.A.; Akimov, A.V.; Babii, M.V. (Bulletin of the Karaganda University. Mathematics Series, 2019)
The optimum content of microtalc (dispersion d = 7...10 µm) and silver carbonate (dispersion d = 0,5 µm) fillers in polymeric materials was determined by the method of mathematical statistics to form an adhesive and functional layers of protective coatings. The mathematical models of physicomechanical and thermophysical characteristics of composites were obtained by the method of statistical processing of the results of the investigation materials.